MatRecData: Material and Process Named Entity Recognition Dataset for EDLC - Miah, Md Saef Ullah; Sulaiman, Junaida; Rajan, Jose; Sarwar, Talha (2023)
This dataset contains material and process data for Electric Double Layer Capacitor (EDLC) data in IOB format. This dataset has been annotated and verified by domain experts. This dataset has 5520 rows and 4 columns. The first column represents the Document ID, the second column represents the Sentence ID, the third column contains the word, and the fourth column contains the material or process tag in IOB format. This dataset contains data for 10 annotated documents among 50 documents.